2022
DOI: 10.1042/bsr20220989
|View full text |Cite
|
Sign up to set email alerts
|

A DCS-related lncRNA signature predicts the prognosis and chemotherapeutic response of patients with gastric cancer

Abstract: The combination of docetaxel, cisplatin, and S-1 (DCS) is a common chemotherapy regimen for gastric cancer (GC) patients. However, studies on long noncoding RNAs (lncRNAs) associated with the chemotherapeutic response to and prognosis after DCS remain lacking. The aim of this study was to identify DCS mRNAs-lncRNAs associated with chemotherapy response and prognosis in GC patients. In this study, we identified 548 lncRNAs associated with these 16 mRNAs in the TCGA and GSE31811 datasets. Eleven lncRNAs were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These genes also play a significant role in DDR ( 53 55 ); nonetheless, the mechanism by which MAGI2-AS3 impacts DDR in GC has yet to be elucidated. Previous research revealed that LINC00106 expression was decreased in cisplatin-resistant GC cell lines and that knocking down LINC00106 enhanced the proliferation and migration of AGS cell lines ( 56 ). Given that cisplatin induces a DNA damage response by binding to DNA ( 57 ), it is possible that LINC00106 is involved in the DDR process and influences the phenotype of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…These genes also play a significant role in DDR ( 53 55 ); nonetheless, the mechanism by which MAGI2-AS3 impacts DDR in GC has yet to be elucidated. Previous research revealed that LINC00106 expression was decreased in cisplatin-resistant GC cell lines and that knocking down LINC00106 enhanced the proliferation and migration of AGS cell lines ( 56 ). Given that cisplatin induces a DNA damage response by binding to DNA ( 57 ), it is possible that LINC00106 is involved in the DDR process and influences the phenotype of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA AC104964.4 expression is associated with the sensitivity to docetaxel, cisplatin, and S-1 (DCS) treatment. Yang et al reported that the expression of the lncRNA AC104964.4 decreased in cisplatin-resistant gastric cancer (GC) cells, suggesting that lncRNA AC104964.4 is involved in the response to chemotherapeutic drugs 41 . It is also negatively related to immune infiltration (neutrophils, mast cells and Treg cells), indicating a relatively good prognosis in patients with GC 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In this review, a total of 17 articles ( Table 3 ) used the differential expression of different functionally related lncRNAs to construct algorithms, so as to provide a basis for guiding clinical prognosis and predicting therapeutic effects. Four articles [ 191 , 192 , 193 , 194 ] used drug-resistant tissues or cells (PR, MDR, and DCSR) for differential lncRNA screening to construct a model. Four articles [ 193 , 194 , 195 , 196 ] constructed prediction models based on pyroptosis-related lncRNAs (PRlncRNAs).…”
Section: Clinical Application Of Drug Resistance-related Lncrnasmentioning
confidence: 99%